The Value of Transitioning From Scoring-Based Peer Review to Peer Learning. (15th July 2022) - Naringrekar, Haresh; Flanders, Adam E.; Roth, Christopher G.
Abstract : In radiology, scoring-based peer review is the dominant model focused on quality assurance, rather than quality improvement. Although designed to decrease diagnostic errors in radiology, this model has had an overall negative effect secondary to its punitive nature and lack of educational benefit. A peer learning-based system helps circumvent these issues through a multitude of ways. These include increasing learning opportunities, identifying system errors that maybe contributing to the misdiagnosis, and fostering a "just" environment where constructive feedback is given to the radiologist. By changing to the peer learning paradigm, this helps increase engagement and satisfaction by participating radiologists to improve patient care.